Malnutrition in Elderly Patients as a Complication of a Drug Therapy: Clinical Pharmacologist's Point of View - A. P. Pereverzev; O. N. Tkacheva; Y. V. Kotovskaya; O. D. Ostroumova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2019)
Malnutrition is a patient's condition with high relevance and importance for elderly patients (most often seen in very old patients >80 years old), since it is associated with a high risk of progressive worsening of their state, prolongation of hospitalization and death. Exposure to some drugs may increase the risk of malnutrition, especially in elderly patients. The purpose of this work is to provide an overview of the causes of malnutrition, focusing on the pharmacological risk factors, as well as to highlight the existing methods of correction of this condition. The authors show that one of the key reasons for developing drug-induced malnutrition is the patients exposure to drugs, that reduce appetite, cause nausea and vomiting, change taste and olfactory sensations, and have anticholinergic effects. Use of pharmacological (additional prescription of drugs for symptomatic therapy, changing the dose, deprescribing drugs, etc.), and nonpharmacological (diet therapy, adding artificial and natural identical flavors, etc.) treatment methods may help to improve state of patients with already developed pathological condition.